Normality and Principal Component Approach Towards Fertility Time Series in Poland and Czechia - Šimpach, Ondřej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The aim of this paper is to analyse changes of trends in time series of age-specific fertility rates (functional data, where fertility rate is a function of women's age) in Poland and Czechia. Data from Eurostat database are available from 1990 to 2014 for both countries. During this period, the behaviour of the population has changed in terms of family planning. The birth of the first child is being continuously postponed to later ages. Also, the fertility rates are lower. However, the situation between Poland and Czechia differs. Therefore, we compare the development. First, it is searched whether and when occurs normal shape of fertility function. Series of Jarque-Bera tests is applied on individual time series (functional data, where fertility rate is a function of women's age). The analysis revealed that occurs normal shape of fertility function in the age groups 15–49+ in both countries during the whole period. It has not been skewed to the right (to higher ages) yet. Second, the medians of fertility rates were analysed using principal components method implemented in “demography” and “rainbow” packages of the RStudio software. The changes in median fertility curves were examined based on two 10- years long time intervals: 1990–1999 and 2005–2014. We found that they were significantly shifted to the right. These results are important for subsequent analyses because for working with demographic data about fertility it is important to consider the most recent data, which are not significantly skewed and influenced by a range of factors. Estimated parameters of shape of fertility function can be also used for predictions
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 431-440
Keywords: normality; principal components method; fertility rates; Poland; Czechia